Produção e caracterização de membranas flexíveis a base de quitosana visando o uso como plataforma de sensores e biossensores - (:unkn) unknown (Universidade Brasil, 2021)
The development of new platforms for (bio) sensors is a growing area of study, as well as the use of new materials in the development of flexible platforms. Among the main characteristics of this type of platform, flexibility, biocompatibility, and non toxicity are desirable, giving the device adaptive potential, allowing it to be used even as wearable sensors. In this context, this research aimed to produce flexible membranes based on chitosan, to be used as a platform for wearable sensors. Membranes were produced using chitosan (Chi) pure or mixed with 10%, 30% and 50% (w/w) of polyethylene glycol (PEG) through the casting technique (solvent evaporation) of film formation. Additionally, a membrane with Chi / 30% PEG and gold nanoparticles (AuNps)was developed, aimingelectric conduction. Membrane characterizations were carried out through infrared absorption spectroscopy (FTIR), resistivity measurements (four points), mechanical tensile testing and thermogravimetric analysis (TGA). The results show that homogeneous and sustainable membranes, with thickness ranging from 20 to 60 µm were obtained. FTIR spectra show the main vibrational bands for Chi, PEG and AuNps chemical groups. Resistivity tests showed that all membranes are resistive to the flow of electric current, and the added concentration of AuNps did not change this property. The use of PEG as a plasticizer improved the mechanical properties of membranes. Tensile strength tests showed that membranes formed by pure chitosan are more resistant to traction and break more easily (less displacement), as those with the addition of 10% (w / w) of PEG (Chi /PEG 10%)were effectively plasticized, proving to be more flexible.TGA curves showed good thermal stability of the membranes, and between 10 and 20% of mass was lost up to a temperature of 200ºC.These results suggest that the membrane produced with Chi/PEG 10% is a promising material for use as a flexible platform.
Keywords: Quitosana; Membranas flexíveis; Plataformas sensoriais; Casting; Engenharia Biomédica (Bioengenharia)